The Powtoon-based Animated Learning Materials to Keep Students Learning from Home Amidst Covid-19 Pandemic - Riskawati Riskawati; Amri Tanduklangi; Alberth Alberth (Halu Oleo University, 2021)
The fast development of science and technology has brought about changes in human life. This applies to all aspects of life including education. In the field of education, teachers are demanded to adjust to the development that they can no longer be dependent just on their textbooks or course books, if they want their teaching to be motivating and successful. They need to be updated with the current development of technology and be creative and innovative in their teaching, hence, need to be technology-literate. Learning interactions no longer take place only in the real, but also in virtual classroom, especially due to Covid-19 pandemic. This paper justifies that Powtoon is a good choice for a teacher because it is not only an application to be used to video-animate teaching materials, but also as a teaching media by which materials can be interestingly presented to keep students learning from home during the pandemic of Covid-19. Moreover, it is also a Learning Management System which a teacher can use to create a virtual classroom. Keywords:Powtoon; Learning Material; Learning from Home; Covid 19 Pandemic